Against the tide: psychodynamic approaches to agitated childhood in France, between crisis and resistance - Céline Borelle; Jean-Sébastien Eideliman; Maïa Fansten; Maëlle Planche; Amélie Turlais
Abstract Is psychoanalysis in crisis? This theme turned out to be recurrent in the comments of professionals working with a psychoanalytical orientation that we encountered during a collective survey on the trajectories of children considered as agitated in France. During this research, we conducted interviews with children and their families, with professionals working in care centres, schools and public administration; we also conducted observations and collected data in care centres. In these places, we observed a diversity of practices, but a clear majority of which claimed to be more or less strictly psychoanalytical or more broadly psychodynamic approaches. After presenting some principles that underlie the psychodynamic approach of agitation, the article discusses the crisis feeling expressed by the professionals met and the reasons that may have caused it. A detour through a reflective analysis of our investigative relationships helps to shed more light on the consequences of this climate on daily work in general and on relations with institutional partners in particular.